ORGANIZATIONAL-ECONOMIC ASPECTS OF SHIPPING COMPANIES BUSINESS DEVELOPMENT ON RUSSIAN SEA CRUISE MARKET - A. Pereverzev (Вестник университета)
In the article the tendencies of development of the Russian sea cruises market are considered, the state of the organization Russian service onboard foreign cruise companies is analyzed, the major cruise companies represented in Russia are highlighted and SWOT-analysis of Russian tour operators is done.